Cardiac plexus of dogs experimentally infected with Trypanosoma cruzi: inflammatory lesions and quantitative studies - Caliari,Marcelo V. (1995)
Qualitative and quantitative aspects of the superficial and profound cardiac plexus of dogs experimentally infected with Be-62 and Be-78 strains of Trypanosoma cruzi were studied. Animals were autopsied in the acute phase of infection. The inflammatory process, lesions and number of parasites were more intense and frequent in animals infected with the Be-78 strain than in those infected with Be-62. Despite this, no statistically significant differences could be found between the number of neuron bodies in the ganglia of infected and control dogs.